On the genus Stephostethus LeConte, 1878 (Coleoptera: Latridiidae: Latridiinae) from Taiwan, with descriptions of two new species - Ho, Yu-Hsiang; Rücker, Wolfgang H.; Chan, Mei-Ling (European Journal of Taxonomy, 2021)
The genus Stephostethus LeConte, 1878 of minute brown scavenger beetles (Coleoptera: Latridiidae: Latridiinae) is recorded from Taiwan for the first time, which extends the southernmost boundary of this genus in the Palaearctic realm. Two new species, S. taiwanus sp. nov. and S. yuanfengensis sp. nov., and one new record, S. chinensis (Reitter, 1877), are described in this study. A taxonomic key to the three species of this genus in Taiwan is also provided. The distributions, habitats and collecting methods of these three species, as well as the structure of the genital segments of this genus are discussed.